2010
DOI: 10.1242/jcs.058602
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Wnt signaling by the nuclear localization of cellular FLIP-L

Abstract: Cellular FLIP (cFLIP) inhibits the apoptosis signaling initiated by death receptor ligation. We previously reported that a long form of cFLIP (cFLIP-L) enhances Wnt signaling via inhibition of β-catenin ubiquitylation. In this report, we present evidence that cFLIP-L translocates into the nucleus, which could have a role in modulation of Wnt signaling. cFLIP-L has a functional bipartite nuclear localization signal (NLS) at the C-terminus. Wild-type cFLIP-L (wt-FLIP-L) localizes in both the nucleus and cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 36 publications
(32 reference statements)
4
28
0
Order By: Relevance
“…While this region shares some homology to the procaspase-8 caspase domain, the cFLIP L caspase-like domain (CLD) lacks caspase activity because there are several amino acid substitutions in the region required for caspase activity (41). The C-terminal region also possesses nuclear localization sequences (NLS) at residues 435–437 and 472–474 (44). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this region shares some homology to the procaspase-8 caspase domain, the cFLIP L caspase-like domain (CLD) lacks caspase activity because there are several amino acid substitutions in the region required for caspase activity (41). The C-terminal region also possesses nuclear localization sequences (NLS) at residues 435–437 and 472–474 (44). …”
Section: Resultsmentioning
confidence: 99%
“…cFLIP L is often regarded as a cytoplasmic protein because it interacts with other cytoplasmic proteins including procaspase-8 (34). However, the cFLIP L C-terminus possesses two NLS’s and it has been shown that cFLIP L is present in the nucleus (44). Thus, it was not surprising to detect wild-type cFLIP L or mutant CLD protein in the nucleus and cytoplasm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, the balance between cFLIP and caspase-8 is of greater importance for the latter in inducing apoptosis than for the former. Further studies underlining the role and mechanism of cFLIP levels and translocation to the cytoplasm by the nuclear export and import signals on cFLIP (30,31) are required to shed light on the nature of this mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The cFLIP gene encodes two isoforms, long and short (29). The cFLIP long isoform (cFLIP L ) contains both nuclear localization and export signals in the caspase-like domain, promoting its translocation into and out of the nucleus (28,30,31). Nuclear translocation of cFLIP was previously described to modulate Wnt signaling, but the apoptotic effect was not addressed.…”
mentioning
confidence: 99%
“…By contrast, c-FLIP L contains a longer C-terminal caspase-like domain, which is not active [18,19]. The structural differences between the c-FLIP isoforms correlate with a different cellular localization and function; indeed, c-FLIP S,R are found in the cytosol alone, whereas c-FLIP L localizes in the nucleus, cytoplasm, ER and Mitochondria-Associated Membranes (MAMs) [20][21][22]. Moreover, whereas the anti-apoptotic role of c-FLIP S,R has been widely demonstrated, c-FLIP L has been reported to exert the opposite effect on apoptosis regulation; c-FLIP L has been shown to block Fas-induced Caspase-8 activation when expressed at high levels, but to act as a pro-apoptotic molecule when its expression level is moderate [23][24][25].…”
Section: Introductionmentioning
confidence: 99%